Bioindicators and human biomarkers as alternative approaches for cost-effective assessment of air pollution exposure - Takano, Ana Paula Cremasco; Rybak, Justyna; Veras, Mariana Matera (Frontiers in Environmental Engineering, 2024)
Traditional methods of air pollution monitoring require substantial investment in equipment and infrastructure. However, efficient and cost-effective alternatives offer promising solutions for regionspecific pollution assessments and understanding their impact on local populations. This review explores examples of low-cost monitoring methods, focusing on natural bioindicators, human interaction-based techniques, and the outcomes associated with air pollution exposure. Bioindicators such as spider webs, lichens, mosses, and Tradescantia pallida (T. pallida) are discussed as potential tools for air pollution monitoring. Human biomonitoring techniques, including the micronucleus assay and the assessment of pulmonary anthracosis, are examined for their ability to provide valuable insights into genotoxic effects and long-term exposure. The advantages and limitations of each method are highlighted. The review advocates for continued research and development to refine these approaches, with the aim of mitigating the adverse health impacts of air pollution on both individuals and communities.